Nutrient Pollution and Its Dynamic Source-Sink Pattern in the Pearl River Estuary (South China) - Tao, Wei; Niu, Lixia; Dong, Yanhong; Fu, Tao; Lou, Quansheng (Frontiers in Marine Science, 2021)
Nutrient enrichment and its quantitative cause-effect chains of the biogeochemical processes have scarcely been documented in the Pearl River Estuary (South China). Field investigations of nutrient samples taken between 1996 and 2018 showed significant differences in nitrogen and phosphorus with times and sites. The concentrations of DIN and DIP gradually increased over the past two decades, with good fitted linear curves (R2 = 0.31 for DIN, R2 = 0.92 for DIP); while the temporal variation in DSi was non-significant. Higher levels of nitrogen and silicate mainly appeared in the upper estuary because of the riverine influence. The phosphorus pollution was accumulated in the northeast (e.g., Shenzhen bay). The aquatic environment was highly sensitive to nutrient pollution and eutrophication risk, which accordingly corresponded to high phytoplankton production and biodiversity. Phosphorus was the limiting factor of phytoplankton growth in this estuary, and more frequently caused the eutrophication risks and blooms. The nutrient pollution was largely influenced by riverine inputs, quantified by PCA-generation, and the contributions of coastal emission and atmospheric deposition were followed. The two-end member mixing model differentiated the physical alterations from the biological activity and identified the dynamic source-sink patterns of nutrient species. Nitrogen and silicate had relatively conservative behaviors in the estuary and phosphate showed an active pattern.